Peningkatan Literasi Keuangan Digital bagi Pelaku UMKM di Era Ekonomi Digital di Sekitar Sekolah Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Ria Rosalia Simangunsong; Rizka Rismawati; Desi Jelanti (Jurnal PKM Manajemen Bisnis, 2026)
The rapid development of the digital economy has required Micro, Small, and Medium Enterprises (MSMEs) to enhance their ability to manage financial transactions through digital platforms. Many local traders still face challenges in understanding and utilizing digital financial tools effectively. This Community Service Program (PKM) aims to improve digital financial literacy among MSME actors around Tajaul Karomatu School in Situ Gadung Village, Tangerang Regency. The activity was carried out on August 19, 2025, by nine lecturers from Universitas Pamulang, involving 30 local traders as participants. The PKM implementation consisted of three stages: preparation, implementation, and reporting. The activities included material presentation, practical sessions, discussions, and a question-and-answer segment. Through these methods, participants were introduced to the concepts of digital financial management, online transaction systems, and the use of digital payment platforms. The results showed an increase in participants’ understanding of digital financial concepts and their confidence in applying them in daily business operations. Furthermore, the participants expressed high enthusiasm and interest in adopting digital tools to improve business efficiency. This PKM activity is expected to encourage the sustainable empowerment of MSMEs in facing the challenges of the digital economy era.